al-Majāz fī Kitābi al-Mahfūẓāti Lishaffi al-Khāmis Bima’hadi Dāru al-Salām Guntūr - Saputra, Mardan; muttaki, muttaki; Daud, Izzat M (Al-Uslub: Journal of Arabic Linguistic and Literature, 2024)
Mahfudzat is a group of words or sentences that have a fixed structure, which usually conveys certain meanings, or a sentence that is concise, contains comparisons, parables, advice on life principles, where mahfudzat consists of poetry, prose, sermons, hadiths of the Prophet, etc. The problem formulation of this analysis is: 1). What types of majaz are found in the fifth grade Mahfudzat book at Pondok Modern Darussalam Gontor? 2). What are the alaqoh contained in the Majaz in the fifth grade Mahfudzot book at the Modern Darussalam Gontor Islamic boarding school? 3). What are the meanings of the Majaz found in the book Mahfudzat Pondok Modern Darussalam Gontor? The purpose of this analysis is to make it easier for students to understand the meaning of Majaz in the fifth grade Mahfudzat book at Darussalam Gontor Islamic boarding school. This research is a type of qualitative research by collecting data sourced from books and other reading materials related to Majaz. Data collection techniques use library techniques, listen and take notes. The data analysis technique uses flowing analysis. This research is a balaghah analysis which focuses on the study of bayan science with one of the discussions being Majaz. There are two Majaz in bayan science, namely Majaz lughowi and Majaz a'qli. Majaz lughawi itself discusses two issues, namely, Majaz Istiarah and Majaz Mursal. From the results of this analysis, the researcher obtained 24 sentences containing different Majaz arrangements according to the type of Majaz itself, including 2 Majaz Aqli 10 Majaz Mursal 4 Majaz isti'arah.